Increased Hepatic Expression of Endothelial Lipase Inhibits Cholesterol Diet–Induced Hypercholesterolemia and Atherosclerosis in Transgenic Rabbits. Issue 7 (July 2017) - Wang, Chuan; Nishijima, Kazutoshi; Kitajima, Shuji; Niimi, Manabu; Yan, Haizhao; Chen, Yajie; Ning, Bo; Matsuhisa, Fumikazu; Liu, Enqi; Zhang, Jifeng; Chen, Y. Eugene; Fan, Jianglin
Abstract : Objective—: Endothelial lipase (EL) is a key determinant in plasma high-density lipoprotein-cholesterol. However, functional roles of EL on the development of atherosclerosis have not been clarified. We investigated whether hepatic expression of EL affects plasma lipoprotein metabolism and cholesterol diet–induced atherosclerosis. Approach and Results—: We generated transgenic (Tg) rabbits expressing the human EL gene in the liver and then examined the effects of EL expression on plasma lipids and lipoproteins and compared the susceptibility of Tg rabbits with cholesterol diet–induced atherosclerosis with non-Tg littermates. On a chow diet, hepatic expression of human EL in Tg rabbits led to remarkable reductions in plasma levels of total cholesterol, phospholipids, and high-density lipoprotein-cholesterol compared with non-Tg controls. On a cholesterol-rich diet for 16 weeks, Tg rabbits exhibited significantly lower hypercholesterolemia and less atherosclerosis than non-Tg littermates. In Tg rabbits, gross lesion area of aortic atherosclerosis was reduced by 52%, and the lesions were characterized by fewer macrophages and smooth muscle cells compared with non-Tg littermates. Conclusions—: Increased hepatic expression of EL attenuates cholesterol diet–induced hypercholesterolemia and protects against atherosclerosis. Abstract : Supplemental Digital Content is available in the text.